Chiral Bifunctional Sulfide-Catalyzed Enantioselective Synthesis of α-Substituted γ-Lactones Bearing a γ-Quaternary Stereocenter - Mori, Taiki; Sumida, Sao; Furuya, Yasuaki; Shirakawa, Seiji (Synlett, 2023)
Catalytic highly enantioselective syntheses of α-spiro-γ-lactones and α-substituted γ-lactones bearing a γ-quaternary stereocenter have been achieved through chiral bifunctional sulfide-catalyzed asymmetric bromolactonizations. The synthetic utility of the optically active γ-lactone products was demonstrated by transformations into functionalized γ-lactones and epoxides possessing a quaternary stereocenter.
Keywords: asymmetric synthesis; halogenation; lactones; organocatalysis; sulfides; bromolactonization